Modernisasi Pengelolaan Koperasi melalui Digitalisasi di Koperasi Mekar, Desa Mudung Darat, Kecamatan Maro Sebo, Kabupaten Muaro Jambi - Dica Lady Silvera; Achmad Hizazi; Heriyani Heriyani; Reka Maiyarni; Aegisia Sukmawati (Universitas 45 Surabaya, 2025)
This community service program focuses on modernizing the management of Koperasi Mekar in Mudung Darat Village, Maro Sebo Subdistrict, Muaro Jambi Regency through the adoption of digital technology. Until now, the cooperative’s transaction recording has been carried out manually using notebooks or Microsoft Excel, which is prone to errors, lacks transparency, and requires a long time to prepare financial reports.To address these issues, the service team conducted training and mentoring on the use of a digital-based savings and loan cooperative application (Kosipanet). The implementation of digitalization is expected to improve efficiency, accuracy, and transparency in financial management. In addition, this activity is also designed to strengthen the human resource capacity of the cooperative, especially the administrators and members, so that they have adequate digital literacy.The success of the program is demonstrated through the administrators’ mastery of the application, the availability of accurate and real-time financial reports, and the increased participation of members in decision-making. Thus, this activity not only promotes professional cooperative governance but also serves as a means of community empowerment based on digital technology, enabling the cooperative to adapt to the digital era and support sustainable local economic development.